Inheritance pattern of first lactation production traits in Murrah buffalo - Vohra, Vikas (Indian Journal of Dairy Science, 2016)
The present investigation was carried out using the performance records pertaining to 707 first lactation Murrah buffaloes maintained at National Dairy Research Institute (NDRI), Karnal were analyzed by least-squares model and to estimate the heritability and genotypic and phenotypic correction of production traits with the help of paternal half-sib correlation method. The least squares means of production traits were 1750.91 kg, 4.33 kg, 7.85 kg, 8.02 kg, 7.86 kg, 7.56 kg, 7.00 kg, 6.49 kg, 5.98 kg, 5.31 kg, 4.83 kg and 4.18 kg for first lactation 305 days milk (FL305DMY) and 11 monthly test day milk records namely, 6th test day milk yield followed by 35, 65, 95, 125, 155, 185, 215, 245, 175 and 305 test day milk yield. Period of calving of animals had significant (pâ‰¤0.01) effect however, season of calving and age at first calving had non-significant effect on first lactation 305 days milk yield. Except TD1, all other monthly test day milk yields were found influenced significantly due to period of calving. Only TD2, TD3 and TD4 milk yields were influenced significantly due to the variation of age at first calving of Murrah buffaloes. The estimates of heritability of all these traits were low to moderate. The estimate of heritability for first lactation 305-days or less milk yield obtained was 0.24 in Murrah buffaloes and first lactation monthly test day milk yield in Murrah buffalo in the present study varied from 0.04 in TD11 MY and 0.21 in TD4 MY. The genetic correlations for all traits were moderate to high except for TD1 with all other test day records. It was observed that TD5 MY (125th day milk yield) had the highest phenotypic correlation with first lactation 305-days or less milk yield in Murrah buffaloes.Â